Standardisation and language criticism in European perspective - Felder, Ekkehard; Manca, Elisa; Weiland, Verena (Handbuch europäische Sprachkritik online, 2018)
This article compares the processes of standardisation that were discussed in the different articles on German, English, French, Italian, and Croatian. It highlights diachronic aspects relating to the shaping of norms for written and spoken language as well as synchronic aspects such as the development of pluricentric standards and issues of orthography. Further, the role of the respective authorities of codification will be discussed from both the diachronic and synchronic perspective.
Gesehen am 04.05.2023